Discovery of the spider family Desidae (Araneae) in South China, with description of a new species of the genus Badumna Thorell, 1890 - Zhu, Ming-Sheng; Zhang, Zhi-Sheng; Yang, Zi-Zhong (Zootaxa, 2006)
A new species of the genus Badumna Thorell, 1890, from Yunnan Province, China is described under the name of B. tangae sp. nov. This is the first Desidae spider discovered and described from China. The new species is similar to B. insignis (L. Koch, 1872) occurring in Japan, Australia and New Zealand. But it differs from the latter by ALE largest; female with epigynal transverse ridge wide and triangular, copulatory ducts with three coils; male palpal tibia with a small, apicomedially placed, retrolateral ventral apophysis.